1999
DOI: 10.1159/000023446
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Autoimmunity in Children and Adolescents with Type 1 Diabetes mellitus

Abstract: Type 1 diabetes is often associated with additional autoimmune phenomena. However, data reported on the frequency of thyroid autoimmunity differ vastly. Therefore, the prevalence of thyroid autoantibodies was evaluated at a large pediatric diabetes center in Southern Germany. 2,305 determinations (TPO and TG, ELISA) were performed in 495 patients with type 1 diabetes (234 boys, 261 girls; age at last measurement: 15.4 ± 0.3 years, duration of diabetes 7.5 ± 0.2 years). The prevalence of elevated thyroid antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
47
4
9

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 13 publications
12
47
4
9
Order By: Relevance
“…Also, in the general population without diabetes, the prevalence of positive test results for thyroid antibodies has been found to increase with age (9). As in previous studies (6,10), female subjects were significantly predisposed to thyroid autoimmunity at any age. Although it is unlikely that association between age or sex and antibody positivity may not exist in the total cohort, we cannot exclude this possibility, because the subset of patients studied was not randomly selected.…”
Section: Resultssupporting
confidence: 53%
“…Also, in the general population without diabetes, the prevalence of positive test results for thyroid antibodies has been found to increase with age (9). As in previous studies (6,10), female subjects were significantly predisposed to thyroid autoimmunity at any age. Although it is unlikely that association between age or sex and antibody positivity may not exist in the total cohort, we cannot exclude this possibility, because the subset of patients studied was not randomly selected.…”
Section: Resultssupporting
confidence: 53%
“…In a study performed in Thailand anti-TPO antibodies were detected 30% in 50 T1D cases and the frequencies were higher in females (27). A study in Giessen demonstrated higher thyroid autoimmunity in girls with T1D and the positive correlation with age (28). Many other studies also found higher prevalences of thyroid autoimmunity in T1D patients (29,30).…”
Section: Discussionmentioning
confidence: 93%
“…In particular, autoimmune thyroid disease (AITD) (Graves' disease and Hashimoto thyroiditis associated with hyper-and hypothyroidism, respectively) and autoimmune type 1 diabetes are often diagnosed in the same subjects [1,2,4,9,10].…”
mentioning
confidence: 99%
“…In addition to associations with HLA class II alleles and haplotypes, notably DRB1*03-DQB1*02 [10][11][12], and the lymphoid-specific phosphatase T cell activation gene, protein tyrosine phosphatase non-receptor type 22 (lymphoid) (PTPN22) [13], AITD and type 1 diabetes have been associated with the cytotoxic T-lymphocyte-associated antigen-4 gene (CTLA4) [5], which encodes a vital negative immunoregulatory receptor in T cell activation and expansion. The association with AITD is strong (odds ratio [OR] ∼1.5) with single nucleotide polymorphisms (SNPs) in the 3′UTR of the gene being the strongest candidates for the causal variant(s) [14].…”
mentioning
confidence: 99%